Migration and survival of Atlantic salmon Salmo salar smolts in a large natural lake. Issue 1 (30th August 2018) - Kennedy, Richard J.; Rosell, Robert; Millane, Michael; Doherty, Dennis; Allen, Michelle
Abstract : An investigation with acoustic telemetry of the passage of Salmo salar smolts through a large natural lake found heavy mortality occurred at the river‐to‐lake confluences (mean 31.2% km −1 ), but was lower in the main body of the lake (mean 2.4% km −1 ). Predation was a significant pressure on emigrating smolts as tagged pike Esox lucius aggregated at river‐to‐lake confluences during the peak of the smolt run. Tagged smolts mainly emmigrated into the lake in the late evening after dusk, possibly as a predator‐avoidance behaviour.